Optimization of catalyst elemental composition and reaction parameters for methanol synthesis on Cu/Zn/Al/Zr catalyst / Dr. Muhammad Zahiruddin Ramli and Nur Iffah Nabihah Muhammad Anuar - Ramli, Muhammad Zahiruddin; Muhammad Anuar, Nur Iffah Nabihah (2020)
Catalytic hydrogenation of methanol involved metal catalyst with its operating reaction parameters such as temperature, pressure, and space velocity. The experimental of methanol synthesis were carried out to characterize a different composition of multi – metallic catalysts consists of Cu/Zn/Al/Zr and also to optimize the catalyst elemental composition as well as reaction parameters via CO2 hydrogenation. The catalyst is synthesized from its metal nitrate with its ratio by co – precipitation (CP) method. CP method included the stages of precipitation, drying, and calcination process to get metal solid catalyst. The catalyst then characterized with BET surface area and Temperature Programme Reducibility (TPR) techniques. Response Surface Methodology (RSM) using Minitab software analyzed the multiple data in order to obtained one set optimum parameter of methanol synthesis. The parameter involved were temperature of 200°C – 300°C, with a pressure ranged of 10bar – 50bar and the conversions of carbon dioxide at 10% - 30%. The data were collected at 10,000h-1 of gas hourly space velocity. This kind of technique is to ensure that all parameter and values covered the boundary of sample. The best catalytic performance of the reaction parameters for methanol synthesis were optimized at the temperature and pressure of 281.11°C and 45.56bar with appropriated conversions at 0.2857 and 0.2661 respectively. The optimum graph has been expressed from the Response Optimizer.